Biochemical characterization of Selaginella 14-3-3 protein isoforms provides insights into the evolution of their phylogenetic groups - Sedlov, Ilya A (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.